(untitled) (International Journal of Engineering and Computer Science, 2015)
Data center have the largest consumption amounts of energy in power sharing. The public cloud workloads contain different priorities and performance requirements of various applications [4]. Cloud data center have capable of sensing an opportunity to present the different programs. The proposed construction and the security level of self-possessed privacy leakage rarely distributed cloud system to deal with the persistent characteristics there is a substantial increases and information that can be used to an enhance the profit, downsizing overhead or both. The mining process of data analysis from different perspectives and summarize it into useful information. Three demonstrable algorithms have been proposed task evaluate the ratios are dissected theoretically and compared using real Internet latency data recital of testing methods.